BREEDING SITES CHARACTERISTICS AND MOSQUITO ABUNDANCE IN SOME SELECTED LOCATIONS WITHIN JIMETA METROPOLIS - Ngwamah, Jacob S.; Atawodi, J. C.; Dakum, Y. D.; Audu-Ohida , H.; Shita, K. B.; Mathias, A. (FUDMA JOURNAL OF SCIENCES, 2025)
Samples of water in the service of mosquito’s breeding, in the tropical region supports their resting, swarming and mating activities. Samples were collected from breeding sites within some selected locations from January to June. One thousand, six hundred and twenty-two (1622) mosquito larvae belonging to 3 genera, Anopheles, Culex, and Aedes were collected and seven species of mosquitoes were identified comprising; Culex quinquefasciatus 410 (25.28%), Aedes aegypti 972(48.83%), Culex decens 42 (2.71%), Aedes vittatus 105 (6.56%), Culex tarsalis 44(2.71%), Culex pipiens 30 (1.85%) and Anopheles gambiae 19(1.17%). Aedes aegypti was common in all the locations. Water samples were collected from seven different major breeding sites such as clocked drainage 154(50.82%), abundant tyres 51(16.39%), Rice farms 45 (12.03%), Pools 19 (5.08%) ponds 42(11.23%), Plastic containers 44 (11.76%), and Metallic containers 19 (5.08%) totaling 374 sampled breeding sites. Out of the 374 selected sites, 251 sites were found positive for different species of mosquito larvae. Correlation analysis showed abundance of mosquitoes decreased with increase in physicochemical parameters. In conclusion, the Aedes aegypti was the most prevalent and present in all the breeding sites with the exception of rice fields; while the physico-chemical parameters were all within the favourable limits for mosquito breeding.